Le Mutisme des Sens [The Deep Silence of the Senses] - Massin, Olivier (Zurich: Olms, 2011)
The thesis defended is that ordinary perception does not present us with the existential independence of its objects from itself. The phenomenology of ordinary perception is mute with respect to the subject-object distinction. I call this view "phenomenal neutral monism" : though neutral monists are wrong about the metaphysics of perception (in every perceptual episode, there is a distinction between the perceptual act and its perceptual objet), they are right about its phenomenology. I first argue that this view is not as counter-intuitive as it might initially seem, by stressing (i) that the lack of presentation of the mind-independence of perceptual objects does not entail their being presented as mind-dependent. (ii) That phenomenal neutral monism is true of ordinary perception in the thin sense, but not in the thick sense (that includes expectations, guesses, feelings etc. grounded on thin perception). (iii) That the concept of a perceptual perspective or point of view should not be confused with the concept of the subject or intentional act of perception. Second, I propose three positive arguments in favor of phenomenal neutral monism. (i) It does justice to the recurring idea that only resistance to our will presents us with the world qua independent from us. (ii) It does justice to the recurring idea that the most natural attitude towards the perceptual world is that of being absorbed in it. (iii) It is entailed by the view that intentional acts are phenomenally transparent (a view held by Russell and Moore, and most contemporary representationalists) together with the view that in order to be presented with a relation (here the act-object distinction) one has to be presented with its relata.